Management of acute appendicitis in adults: A practice management guideline from the Eastern Association for the Surgery of Trauma. Issue 1 (July 2019) - Rushing, Amy; Bugaev, Nikolay; Jones, Christian; Como, John J.; Fox, Nicole; Cripps, Michael; Robinson, Bryce; Velopulos, Catherine; Haut, Elliott R.; Narayan, Mayur
Abstract : BACKGROUND: Acute appendicitis (AA) has been considered one of the most common acute surgical conditions in the world. Recent studies, however, have suggested that nonoperative management (NOM) with a course of antibiotics (ABX) may be as effective as surgery in treating appendicitis. As there are evolving perspectives regarding the optimal therapy for appendicitis, we sought to provide recommendations regarding the role of NOM with the administration of antibiotics (antibiotics-first approach) in uncomplicated AA as well as the need for routine interval appendectomy (RIA) in those presenting with appendiceal abscess or phlegmon (AAP) initially managed without appendectomy. METHODS: A writing group from the Guidelines Committee of the Eastern Association for the Surgery of Trauma (EAST) performed a systematic review and meta-analysis of the current literature regarding appendicitis in adult populations. The Grading of Recommendations Assessment, Development and Evaluation methodology was applied and meta-analyses and evidence profiles generated. RESULTS: When comparing antibiotics-first therapy to surgery for uncomplicated AA in adult populations, we found that perforation and recurrence of disease were the only outcomes consistently represented in the literature. For perforation, we were unable to make a definitive conclusion based on the degree of heterogeneity among the six randomized controlled trials reviewed. The risk of recurrence at 1 year with antibiotics-first treatment was 15.8% (95% confidence interval, 12.05–118.63). Critical outcomes could not be evaluated with the current literature. In NOM patients for AAP, the risk of recurrence was 24.3% if RIA was not performed (95% confidence interval, 2.74–73.11). CONCLUSION: Based on the completed meta-analysis and Grading of Recommendations Assessment, Development and Evaluation profiles, we were unable to make a recommendation for or against the antibiotics-first approach as primary treatment for uncomplicated AA. For NOM with AAP, we conditionally recommend against RIA in an otherwise asymptomatic patient. This review reveals multiple limitations of the published literature, leaving ample opportunities for additional research on this topic. LEVEL OF EVIDENCE: Systematic review, level II.